Adaptive Data Aggregation for Shortest Geopath Routing Protocol in Wireless Sensor Network - Ady Kusuma, I Gusti Ngurah; Wibisono, Waskitho (IPTEK The Journal for Technology and Science, 2017)
Wireless sensor network is a network that contains many nodes in each nodes with limited power source and ability to send a sensing data to a cordinator node that called sink node. Every data that sent through network, will cost amount of energy for transmitting and draw energy each time a data transmitted from power soucve. To extend the network lifetime, we should optimize the data that transmitted. In this research author propose an adaptive method that using in network data aggregation with cluster and tested in SIDnet-SWANS. This method collecting the data at Cluster Head node before it forward to sink node rather than forwarding every data that arrive at cluster head to next hop. This method has better performance than other method, average energy left after 48 hours sensing is 17.23% and 78818.67 second to first node dead. This method giving more efficiency of energy use better than non-aggregation method